Porcelain Gallbladder: Decoding the malignant truth - Machado, Norman O. (Sultan Qaboos Univ Med J, 2016)
Gallbladder calcification, also referred to as porcelain gallbladder, has received significant attention in the medical literature due to its perceived role in increasing the risk of developing a gallbladder carcinoma. However, recent reports raise questions challenging this purported high risk. While previous studies reported a concomitant incidence of gallbladder cancer in porcelain gallbladder ranging from 7–60%, more recent analyses indicate the incidence to be much lower (6%). Based on evidence in the current literature, a prophylactic cholecystectomy is not routinely recommended for all patients with porcelain gallbladder and should be restricted to those with conventional indications, such as young patients. However, it is important to note that a nonoperative approach may require prolonged follow-up. A laparoscopic cholecystectomy is a feasible therapeutic option for patients with porcelain gallbladder, although some researchers have indicated a higher incidence of complications and conversion due to technical difficulties.